Physico-chemical and Mineral Composition of White Seeded Raisin Varieties (Vitis vinifera L.) Grown under Semi-arid Condition - , R. G. Somkuwar; , A. K. Upadhyay; , A. K. Sharma; , P.S. Karande; , R. D. Nale (Archives of Current Research International, 2024)
Raisins (dried grapes) are preferred for their distinctive, delightful flavor, high nutritional content, and their potential to lower the risk of several serious and chronic conditions. The quality of raisins is crucial, as it has a direct impact on the health and well-being of those who consume them. The present study assessed the physiochemical composition, mineral content, and sensory parameters of white seeded raisins. The physiochemical parameters such as raisin weight, raisin recovery, pH, moisture, ash, carbohydrate, protein, and mineral content (potassium, phosphorus, calcium, magnesium, sodium, copper, iron, and zinc) were assessed. Result revealed that the grape variety Pandhari Sahebi showed higher raisin weight and protein content. Hussain Kadu recorded maximum moisture and carbohydrate content. Significantly, higher potassium and iron content was noted in Hussain Kadu. Based on the results, Hussain Kadu was preferred for raisin colour, texture and overall acceptability.